The Influence of Celebrity Endorser, Brand Image, and Brand Trust on Consumer Purchasing Decisions of Nike Brand Sport Shoes In Surabaya - Prananda Yudhistira Putra; Soebandhi Ningrum (NAROTAMA UNIVERSITY, Indonesia, 2019)
This study aims to analyze the influence of celebrity endorser, brand image, and brand trust on consumer purchasing decisions for Nike Brand Sports Shoes in Surabaya. This research is quantitative research. Population and sample based on questionnaire distribution to consumers who have already bought and used Nike brand sports shoes in Surabaya were taken as many as 180 respondents. Data collection techniques using interviews, observation and questionnaires. The data analysis used is validity test, reliability test, classic assumption test, multiple linear analysis test and hypothesis test. Research results of variable celebrity endorser, brand image and brand trust have a significant simultaneous effect partially on the purchase decision of Nike brand sports shoes in Surabaya where a significant value is smaller than 0.05.